INTERNATIONAL ATTITUDE TO CULTURAL GENOCIDE PREVENTION IN NAGORNO-KARABAKH: A LINGUISTIC PERSPECTIVE - Khazhakyan, Mariam (Armenian Folia Anglistika, 2025)
The present study is an attempt to examine the tragic consequences of genocides in general, with a particular focus on cultural genocides. Cultural genocide, though not explicitly identified in international law, represents a profound and insidious form of destruction aimed at eradicating the cultural, religious, and social foundations of a group. The cultural genocide in Nagorno-Karabakh (Artsakh), the destruction of its cultural legacy, continues to demand urgent attention. Hence, we aim to highlight the true picture of cultural genocide through a prosodic and linguistic analysis of speeches – both written and spoken – by prominent American and European politicians. The purpose is to underscore the critical importance of preserving cultural identities and to advocate for the formal recognition of cultural genocide in international law. Acknowledging both physical and cultural genocides allows for a more comprehensive strategy for preventing and responding to the destruction of communities and their unique legacies. Combining historical research with prosodic analysis of political speeches delivered between 2020 and 2023, this article explores how vocal elements such as intonation, stress, and rhythm reflect global attitudes toward the cultural erasure of Nagorno-Karabakh. The findings reveal that these speech patterns often mirror geopolitical positions – some conveying urgency, others indifference – shaping public awareness and political engagement. The study calls for the equal recognition of physical and cultural genocides to ensure the full protection of vulnerable groups and stronger mechanisms for international accountability.